MOTIVASI, DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI RUMAH SAKIT - Indah Jailani (LPPM Universitas Awal Bros, 2021)
Motivation is a factor that encourages someone to do a certain activity, good discipline can show the level of responsibility in the individual for the tasks that have been given and organizational culture is a framework that guides daily behavior and makes decisions for employees and direct their actions to achieve organizational goals. performance is the implementation of employee responsibilities with the achievement of work results in accordance with the quality and quantity that exists within the company. The method used is observation and documentation. The results show the effect of motivation, work discipline and organizational culture on performance.